Redefining learning: student-centered strategies for academic and personal growth - Bhardwaj, Vipul; Zhang, Shuwei; Tan, Yan Qin; Pandey, Vijay (Frontiers in Education, 2025)
As the landscape of higher education continues to evolve, institutions must adapt to meet the changing needs of prospective graduate students. This article explores the implications of student-centered strategies on the academic and personal growth of graduate science students. The traditional teacher-centered approach, while effective in conveying foundational knowledge, has been criticized for hindering the development of critical thinking, creativity, and problem-solving skills. In contrast, the student-centered approach shifts the focus to learners, encouraging active participation and fostering essential skills needed to address modern scientific challenges. The teaching concepts, “for the student,” “of the student,” and “by the student” emphasize inclusivity, peer collaboration, and encouraging students to take ownership of their education. A prime example of the success of this approach is the ‘’Molecular Basis of Cancer’’ course, which transitioned from a traditional teacher-centered model to a student-centered one. This shift has allowed students to engage more deeply with complex scientific concepts, fostering independent learning, peer-led discussions, and collaborative research. The results of this transition are evident not only in improved academic performance but also in significant scientific outputs, such as published research articles co-authored by students. By encouraging critical inquiry, creativity, and a professional attitude, the course enables graduate students to navigate real-world scientific challenges more effectively. This case study highlights the accomplishments of student-centered model while identifying areas for further improvement in teaching practices and curriculum design. It underscores the importance of student-centered teaching in shaping future scientific leaders by providing a more balanced, dynamic, and inclusive learning environment for graduate students in science-education. As education continues to evolve, blending traditional methods with student-centered approaches will be key to creating engaging and empowering educational experiences that meet the demands of both students and the ever-advancing fields of science and technology.